Growth, carbon assimilation and biochemical changes of oil palm seedlings (Elaeis guineensis Jacq.) in climate change factors with potassium fertilisation - Tuan Syaripah Najihah binti Tuan Mohd Razali
The demand for palm oil is expected to increase due to the increase in world population. However, climate change poses significant challenges to the production of oil palm as its output can be directly affected by abiotic stress, especially water and temperature stress. Potassium (K) is a crucial element in oil palm plantation as it is directly involved in the crop physiological processes. Thus this research was designed to determine how the use of the evapotranspiration replacement (ER) method and potassium fertiliser could be used to alleviate water and heat stress in oil palm seedlings. In tile first experiment, four irrigation regimes [100% ER (well -watered), 75% ER (moderate water stress), 50% ER (high water stress), and 25% ER (severe water stress)] were used to investigate the effect of different water stress regimes on the physiology of 4-montlls old oil palm seedlings. Results showed that severe water stress decreased vegetative plant growth, plant water status, leaf gas exchange, water use efficiency (WUE), and fv/fm (maximwn efficiency of photosystem II), but the malondialdehyde (MDA) and proline levels of oil palm seedlings were increased. In the second experiment, tluee levels of potassium rates (Kl, K2, and K3) with five times applications (170, 340, and 510 kg KCI ha "), (480 960, and 1440 kg KCI ha") (170,340, and 510 kg KCI ha-I), (960, 1920, and 2880 KCI kg ha "), and (960, 1920, and 2880 kg KCI ha-I) under three different levels of water stress (100% ER, 75% and 25% ER) were exposed on oil palm seedlings to identify the best rate of potassium fertiliser under water stress application and to understand the interaction between drought impacts and potassium application on oil palm seedlings. The result revealed that water stress hampered the growth of oil palm seedlings. As potassium fertiliser rates increased, no significant differences in the physiology of the seedlings were observed except for height, net photosynthesis, and intercellular C02 (C). However, the biochemical properties (proline, soluble sugars, and phenolics) of oil palm seedling increased by 50%, 60%, and 55% while MDA decreased by 40% compared to control when the application ofK was doubled. Yet, there were no significant differences by applying double rate and triple rate of K. There was also an interaction between different water treatment levels and the rate of potassium fertiliser on the height, C; and flavonoid level of oil palm seedlings. In the third experiment, three types of potassium fertiliser (KCI; Potassium chloride, K2S04; Potassium s Ilphate and KN03: Potassium nitrate) with a double rate of K under three levels of wat r stress (100% ER, 75% ER, and 25% ER) were exposed to oil palm seedlings to investigate the influence of potassium source in minimizing water stress effects in this crop. It was found that as the level of water reduced, the RGR (relative growth rate), LAR (leaf area ratio), L WR (leaf weight ratio) and SLA (specific leaf area) of oil palm seedlings reduced, but the value of R:S (root: shoot ratio) improved. The result also revealed that K2S04 increased the leaf gas exchange and fvlfm as well as reducing the leaf temperature compared to KCI and KN03. There was an interaction between water stress and the source of K on respiration rate and electrolyte leakage. K2S04 also reduced the biochemical properties of oil palm seedlings. In the last experiment, the study was designed to investigate the effect of elevated temperature on the physiology of oil palm seedlings, to examine the combination of heat and water stress as well as to explore the potential of potassium fertiliser in alleviating these stresses. Oil palm seedlings were treated with six regimes: